PENGARUH KINERJA LINGKUNGAN, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, RETURN ON ASSET, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Hartanti, Rina; Marwah, Fadillah; Amalina, Nurhafifah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study aims to analyze the Effect of Environmental Performance, Dividend Policy, Company Size, Return On Assets, and Leverage on Company Value. The sample of this research is Coal Mining Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period and have participated in the Ministry of Environment's PROPER program during that period. The research sampling was determined by purposive sampling, of the 75 company data observed, only 15 companies met teh criteria for were then analyzed using Regression Analysis with Panel Data. The results of the study indicate that Environmental Performance and leverage have a negative effect on Company Value, while Dividend Policy, Company Size, Return On Assets have a positive effect on Company Value.